DIGITAL TRANSFORMATION OF ISLAMIC BANKING IN INDONESIA: ANALYZING OPPORTUNITIES, CHALLENGES, AND STRATEGIES FOR ENHANCING COMPETITIVENESS IN THE DIGITAL ECONOMY ERA - Zulkipli Zul (PT. Samudra Solusi Profesional, 2026)
This study aims to analyse the digital transformation strategies implemented by Islamic banks in responding to challenges whilst capitalising on opportunities in the digital age. The primary focus of this study is the relationship between technological innovation and compliance with Sharia principles, as well as how digitalisation strategies can strengthen the competitiveness of Islamic banking without compromising the integrity of Islamic law. The methodology employed is a descriptive qualitative approach through a literature review, examining various academic references such as national and international journals, regulatory reports (from the OJK and Bank Indonesia), and strategic documents from leading Islamic banks. This secondary data was systematically analysed to identify opportunities, challenges, and actual strategies implemented. The findings indicate that digitalisation presents significant opportunities for expanding Islamic financial inclusion, operational efficiency, and technology-based product innovations such as e-mudharabah, e-wakaf, and mobile zakat. However, the main challenges faced include regulatory frameworks that have yet to adapt, data security risks, disparities in digital infrastructure, and a shortage of human resources with dual expertise (in digital technology and Sharia law). The proposed strategies include strengthening the digital Sharia ecosystem, collaborating with halal fintech firms, adopting innovative technologies such as AI and open banking APIs, and providing staff training based on the integration of technology and fiqh muamalah. Through a holistic approach, digital transformation is expected to consolidate the position of Sharia banking as a pillar of the modern Islamic economy that is inclusive, efficient, and sustainable.